Primary pulmonary hyalinizing clear cell carcinoma with EWSR1 gene translocation: a case report - Jian, Can-hui; Luo, Shuai; Wang, Jin-jing (Frontiers in Oncology, 2024)
BackgroundPrimary pulmonary hyalinizing clear cell carcinoma (HCCC) is a rare type of primary salivary gland-type tumor of the lung. HCCC is characterized by unique pathological features, including nests, cords, or trabeculae of clear or eosinophilic tumor cells infiltrating a mucinous or hyalinized stroma. Additional analyses of this carcinoma have revealed positive epithelial markers via immunophenotyping and EWSR1 gene translocation through genetic testing. However, the morphology of HCCC has been found to change during bronchoscopic biopsy, suggesting certain challenges for its clinical diagnosis and treatment.Case presentationA 47-year-old female patient presented with a 2-month history of cough, sputum production, and dyspnea. A chest CT scan found a nodular soft tissue density shadow in the lower segment of the trachea. Subsequently, the patient underwent tumor resection via combined flexible and rigid bronchoscopy. Postoperative pathological examination, including immunohistochemistry and molecular testing, confirmed an EWSR1 gene translocation. The final pathological diagnosis was primary pulmonary HCCC. A follow-up at 6 months post-surgery showed mediastinal lymph node metastasis.ConclusionsPrimary pulmonary HCCC is an extremely rare, low-grade malignant epithelial tumor of the lung, which has a notably difficult clinical diagnosis and treatment due to the absence of a standard treatment protocol. This case report presents a patient with primary pulmonary HCCC confirmed by molecular testing, aiming to raise awareness about this tumor among physicians and provide valuable clinical references.